Evaluation of Umbilical Cord-derived Mesenchymal Stem Cells (UC-MSCs) Exosome Implantation and Platelet-Rich Fibrin (PRF) on Critical Long Bone Defects in Sprague-Dawley Rats - Dilogo, Ismail Hadisoebroto; Reksodiputro, Mirta Hediyanti; Antarianto, Radiana Dhewayani; Makabori, Januar Chrisant Fladimir; Kousar, Iqra (Journal of Neonatal Surgery, 2025)
Critical bone defect is a loss of bone structure that exceeds the critical size of the bone's ability to regenerate. Autologous bone grafting is the standard therapy used in extensive bone defects. However, it is associated with various morbidities. Thus, the use of exosome obtained from umbilical cord mesenchymal stem cell (UC-MSC) and PRF is promising and can be a potential alternative to treat critical bone defects. This study was an experimental post-test only control group design that used 30 Sprague Dawley rats aged 8-12 weeks, weighing about 250-300 grams. The rats were then divided into 5 treatment groups, namely hydroxyapatite (HA) and bone graft (group I), HA, bone graft, and PRF (group II), HA, bone graft and exosome from UC-MSC (group III), HA, bone graft, PRF, and exosome from UC-MSC (group IV), and HA, PRF, and exosome from UC-MSC (group V). In each rat, a 5mm femoral bone defect was created and internally fixated using a 1.0-1.2 mm K-wire threaded. At the fourth week of follow-up, RT-PCR examination was performed to assess BMP-2 and chordin levels, as well as histomorphometry examination to measure the percentage of ossification area, fibrotic area, and void area. . One-way ANOVA and post-hoc tests were perfomred using SPSS version 26 for the analysis.In the RT-PCR examination, the highest BMP-2 gene expression was found in group I (1.0 - 1.5; median 1.2), followed by group II (0.2 - 1.2; median 0.5), group IV (0.3 - 0.7; median 0.4), group III and group V. Meanwhile, chordin gene expression was highest in group III (0 - 50), followed by the other groups with similar values. However, descriptive analysis showed no significant correlation between BMP-2 and chordin levels in critical bone defects, with p values of 0.096 and 0.690 each. Statistical analysis showed significant results for BMP-2 (p = 0.017) and no significant results for chordin (p = 0.269). Furthermore, the histomorphometry analysis for ossification, fibrotic, and void area showed no statistical significance (p > 0.05). The use of PRF and exosomes from SPM-TP separately showed different results, where PRF showed good results in osteogenesis and exosomes from SPM-TP showed higher results in fibritic tissue formation. However, the use of both exosomes and PRF together has not been studied for their effect on critical bone defects. In this study, the opposite results were found instead of the expected results. This may indicate that the combination of PRF and exosome from UC-MSC could possibly yield a negative effect on osteogenesis. The combination of PRF and exosome from UC-MSC did not yield positive effect on the outcomes examined in this study